Visualizing and assessing the size-dependent oral uptake, tissue distribution, and detrimental effect of polystyrene microplastics in Eisenia fetida. (1st August 2022) - Xiao, Xue; He, Erkai; Jiang, Xiaofeng; Li, Xing; Yang, Wenjun; Ruan, Jujun; Zhao, Chunmei; Qiu, Rongliang; Tang, Yetao
Abstract: Microplastics are widely distributed in the environment, their potential ecological risks on soil organism have attracted extensive attention, while the investigation of the size effect on its accumulation and toxicity in soil invertebrates are still lacking. In this study, we set out to explore the size-dependent effects of microplastics on soil invertebrates with different doses. Specifically, we investigated the effect of polystyrene (PS) microplastics on earthworm Eisenia fetida with three different sizes (70 nm, 1 μm and 10 μm) and exposure doses (0.5%, 5% and 10% w/w in food). Results showed that PS microplastics had no effects on the mortality of E. fetida, while an obvious growth inhibition with rising exposure concentrations was observed, especially under exposure of 70 nm plastic particles. Additionally, 70 nm PS microplastics induced more serious oxidative stress, energy depletion and histopathological damage on earthworms compared with larger sizes. The accumulation and distribution pattern of microplastics was size-dependent in earthworms after 3- and 7-day exposure as revealed by laser confocal microscopy. Notably, earthworms accumulated more micro-sized particles (MPs, 10 μm and 1 μm) but with less toxic responses, suggesting its weaker toxicity. The distribution pattern of MPs may explain the weak relation between accumulation and toxicity as they mainly distributed in epidermis of mid- and tail-section and the intestine of earthworm. In contrast, nano-sized particles (NPs, 70 nm) were more distributed in the head-section and subcutaneous tissue of the skin, which was in accordance with the obvious toxic responses found in earthworms exposing to NPs. Our study highlighted the importance of size in determining the accumulation, distribution and toxic effects of plastic particles towards soil invertebrates and advocates the necessity of ecological risk assessments of NPs. Graphical abstract: Image 1 Highlights: NPs exhibited greater inhibition on the growth of earthworm than MPs. Oxidative stress, energy depletion and histopathological damage were induced by MPs. Earthworms tended to accumulate more plastic particles with larger size. MPs mainly distributed in the epidermis of mid/tail and intestine of worms. NPs mainly distributed in worm head and the subcutaneous tissue of skin.